CYTOMORPHOLOGICAL EVALUATION OF THYROID LESIONS USING THE BETHESDA SYSTEM: A STUDY OF 320 CASES - Pawar, Sumana; Chandan, Rajesh H.; Kolavi, Suwarna Siddappa (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Introduction: Thyroid nodules are common clinical findings and require accurate evaluation to differentiate benign from malignant lesions. Fine Needle Aspiration Cytology (FNAC) is widely used as a first-line diagnostic tool. The Bethesda System for Reporting Thyroid Cytopathology (TBSRTC) provides a standardized reporting system. Aim: To evaluate thyroid lesions using FNAC and classify them according to the Bethesda system. Materials and Methods: This study included 320 patients presenting with thyroid swelling. FNAC was performed and smears were categorized according to the Bethesda system. Results: Out of 320 cases, satisfactory cytological smears were obtained in 310 cases (96.8%) while 10 cases (3.1%) were non-diagnostic. The majority of cases belonged to Bethesda Category II (Benign) accounting for 89.3% cases. Category III (AUS) constituted 0.6% cases, Category IV (Follicular Neoplasm) 1.25%, Category V (Suspicious for Malignancy) 3.4%, and Category VI (Malignant) 2.18%. Conclusion: FNAC using the Bethesda system is a reliable, simple, and cost‑effective diagnostic modality for the evaluation of thyroid lesions.